2016
DOI: 10.1021/acs.jpcc.6b10688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Confinement of LiNH2 on Ammonia Decomposition Catalysis and the Storage of Hydrogen and Ammonia

Abstract: LiNH2 is of interest to several aspects of energy storage such as reversible hydrogen storage, battery technology, catalysis, and ammonia capture/storage. We investigated the impact of nanoconfinement in carbon scaffolds on the hydrogen and ammonia release properties of LiNH2 and its catalytic activity in NH3 decomposition. Ammonia release from macrocrystalline LiNH2 begins at 350 °C, while confined LiNH2 releases ammonia from below 100 °C under helium flow. This ammonia release consisted of 30.5 wt % ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
0
28
0
2
Order By: Relevance
“…Further studies showed that other alkali and alkaline earth metal amides/imides could also synergize with 3d TM(N) or Ru to exhibit superior catalytic activities . Confining LiNH 2 and Ni in carbon scaffolds leads to enhance catalytic activity in ammonia decomposition that is comparable to that of the commercial Ru‐based catalyst 2Li3FeN2+NH33Li2NH+Fe2N+1/2N2 3Li2NH+Fe2N2Li3FeN2+3/2H2…”
Section: Complex Hydrides For Catalysismentioning
confidence: 99%
“…Further studies showed that other alkali and alkaline earth metal amides/imides could also synergize with 3d TM(N) or Ru to exhibit superior catalytic activities . Confining LiNH 2 and Ni in carbon scaffolds leads to enhance catalytic activity in ammonia decomposition that is comparable to that of the commercial Ru‐based catalyst 2Li3FeN2+NH33Li2NH+Fe2N+1/2N2 3Li2NH+Fe2N2Li3FeN2+3/2H2…”
Section: Complex Hydrides For Catalysismentioning
confidence: 99%
“…[105a,108a] de Jongh et al, on the other hand, used a melt infiltration method to stabilize/confine alkali metal amides (LiNH 2 , NaNH 2 , or KNH 2 ) within the pores of carbon matrix. [109] The interaction of amide and carbon support may prevent the loss of amide from the catalyst and mitigate the stability issue to a certain extent. However, the formation of side product (cyanamide) may lower the catalytic activity.…”
Section: Catalytic Thermal and Electrochemical Ammonia Decompositionmentioning
confidence: 99%
“…The Jongh group used confinement inside porous carbon structures to tackle the H 2 storage challenge. 56 LiNH 2 is a strong H 2 carrier candidate, but it has the drawback of only releasing H 2 at temperatures above 300 °C. Ammonia is another H 2 carrier option, but the current commercial catalyst for NH 3 conversion to H 2 is based on Ru, an expensive metal.…”
Section: Confinement In Pores and Cavitiesmentioning
confidence: 99%